2014
DOI: 10.1242/jcs.143602
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of stereocilia and apical junctional complexes by Cdc42 in cochlear hair cells

Abstract: BSTRACTCdc42 is a key regulator of dynamic actin organization. However, little is known about how Cdc42-dependent actin regulation influences steady-state actin structures in differentiated epithelia. We employed inner ear hair-cell-specific conditional knockout to analyze the role of Cdc42 in hair cells possessing highly elaborate stable actin protrusions (stereocilia). Hair cells of Atoh1-Cre;Cdc42 flox/flox mice developed normally but progressively degenerated after maturation, resulting in progressive hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 69 publications
5
64
1
Order By: Relevance
“…Fused stereocilia were also reported in early studies of noise damage 61 . We note that the damaged outer hair cells phenocopy a conditional loss-of-function Cdc42 mutant 65 . Cdc42 is a member of the Rho sub-family of small GTPases that regulates the assembly of actin-rich cellular structures 66 .…”
Section: Discussionmentioning
confidence: 82%
“…Fused stereocilia were also reported in early studies of noise damage 61 . We note that the damaged outer hair cells phenocopy a conditional loss-of-function Cdc42 mutant 65 . Cdc42 is a member of the Rho sub-family of small GTPases that regulates the assembly of actin-rich cellular structures 66 .…”
Section: Discussionmentioning
confidence: 82%
“…We previously reported inner ear HC‐specific Cdc42‐knockout (KO) mice, which show progressive deafness in parallel with HC loss with stereocilia degradation, including short, elongated, fused stereocilia (Ueyama et al , ). Furthermore, we found that the amount of active RhoA (GTP‐form) is increased in Cdc42‐knockdown (KD) cells (Ueyama et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Stereocilia bundle formation follows the boundary of these domains, with the vertex of the bundle attached to the kinocilia and the tallest stereocilia forming closest to the lateral side of the cell in a decreasing height gradient to the medial side. Phenotypes similar to mutants lacking kinocilia also arise when non-ciliary proteins are lost that regulate basal body positioning through organization of the microtubule network, including the small GTPases Cdc42 and Rac1 [4851]. Thus, proper cortical-microtubule interactions are critical for positioning kinocilia in their correct location, and ultimately orienting the newly formed bundles properly along the medial-lateral axis.…”
Section: Development Of Stereociliamentioning
confidence: 99%